Syllable-based reading improvement: Effects on word reading and reading comprehension in Grade 2. (April 2020) - Müller, Bettina; Richter, Tobias; Karageorgos, Panagiotis
Abstract: This study examined the effects of a syllable-based reading intervention for German second graders who demonstrated difficulties in the recognition of written words. The intervention focused on fostering word reading via syllable segmentation. The materials consisted of the 500 most frequent syllables typically read by 6- to 8-year-old children. The aims were to practice phonological recoding, consolidate orthographic representations of syllables, and routinize the access to these representations. Compared to children randomly assigned to a wait-list group, poor readers in the treatment condition showed significant improvements in standardized measures of phonological recoding, direct word recognition, and text-based reading comprehension after the 24-session intervention. Poor readers in the treatment condition also showed greater improvements in development of word recognition compared to children with efficient word recognition skills. The results provide evidence that a syllable-based reading intervention is a promising approach to increase struggling readers' word recognition skills, which in turn will improve their reading comprehension. Highlights: Effects of a syllable-based word reading training in Grade 2. Training based on the 500 most frequent syllables in German. Poor readers' visual word recognition and reading comprehension benefited. Effect on reading comprehension fully mediated by improvements in word reading.